Experiência prática internacional durante a graduação em medicina - Meira, Thauanna Alves (Universidade Federal de São Carlos, 2023)
This Final Paper is a reflection on the trajectories experienced during medical graduation at a Brazilian public university. Among the aspects addressed are the form of selection for the course, the active teaching methodology, the resources needed to carry out an exchange during graduation and the international practical experience lived at the University Hospital of Odense, in Denmark.
International practical experience during medical school
Keywords: Metodologia ativa; Intercâmbio; Dinamarca; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM